The immune system as a victim and aggressor in chronic obstructive pulmonary disease - McGrath, Joshua J. C.; Stampfli, Martin R. (Journal of Thoracic Disease; Vol 10, Supplement 17 (June 20, 2018): Journal of Thoracic Disease, 2018)
Chronic obstructive pulmonary disease (COPD) is a debilitating respiratory disorder defined by progressive and largely irreversible airflow limitation (1).